2012
DOI: 10.1016/j.jfoodeng.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extraction of anthocyanins from Hibiscus sabdariffa: Experimental kinetics and modeling

Abstract: Extraction of glucomannan from crude porang flour by acid hydrolysis and ethanol precipitation was studied. Effects of acid concentration, temperatures and time were investigated, kinetics model of the process was developed and the parameters were evaluated based on experimental data. New data on yield and purity of glucomannan under various conditions were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
82
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 38 publications
12
82
0
2
Order By: Relevance
“…Concentration was expressed as delphinidin 3-D-xylosylglucoside equivalents (molecular weight 577 g mol −1 ). The molar extinction coefficient at pH 1 and 510 nm used for calculation was 26 000 L mol −1 cm −1 (Cissé et al, 2012).…”
Section: Total Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration was expressed as delphinidin 3-D-xylosylglucoside equivalents (molecular weight 577 g mol −1 ). The molar extinction coefficient at pH 1 and 510 nm used for calculation was 26 000 L mol −1 cm −1 (Cissé et al, 2012).…”
Section: Total Anthocyaninsmentioning
confidence: 99%
“…Such modifications make distinguishing the calices of one variety from another harder and reduce the accuracy. This task is obviously even more difficult when the calices are turned into powder before the pigment extraction process (Cissé et al, 2012). So, the aim of the study was to elaborate a more rigorous discrimination method that can be easily applied at different steps of processing.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that in the reportscited above, researchersdo not mention the average particle size; they only allude the use a ground Roselle calyces. Cissé et al (2012) evaluated the solid-liquid extraction process for the production of anthocyanins from Roselle. They reported that the calyces: solvent ratio and particle size were the main factors affecting the efficiency of extraction of anthocyanins.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 99%
“…Therefore, the average particle size, the extraction temperature, the type of solvent, and the solid-solvent ratio have a significant impact on the extraction of bioactive compounds of parts of plants. It has been shown that the yields of anthocyanins, by extraction with solvents, increases as the particle size of Roselle calyces decreases (Cissé et al, 2012). Also, the increase of the solid-solvent ratio improves the yields of phenolic compounds in the extract (Dai & Mumper, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, long operating times, high energy demand and elevated solvent consumption (Cissé et al, 2012;Shirsath et al, 2012) are required in conventional extraction systems. These facts, linked to the increasing human use of phenolic compounds from natural sources, has promoted the development of new extraction methods based on non-toxic solvents and the application of auxiliary energy sources for the purposes of accelerating the extraction processes.…”
Section: Conventional Methodsmentioning
confidence: 99%